Use of Pulse-Energized Electrostatic Precipitator to Remove Submicron Particulate Matter in Exhaust Gas - Vishnu Thonglek; Tanongkiat Kiatsiriroat (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
An electrostatic precipitator (ESP) with negative pulse corona discharge for removal of submicron particles in the exhaust gas of thermal equipment such as boilers, burners or internal combustion engines is presented. A wire-cylinder ESP was designed and constructed for experimental testing at laboratory scale. The collection efficiency of submicron particles in the exhaust gas of a diesel burner under various dust loadings and gas velocities was investigated. The results were compared with those obtained from the conventional DC ESP technique. It was found that the pulse peak voltage supply could be set much higher than the sparking limit of the DC energized unit. Thus, the electric field density could be increased, which resulted in a higher collection efficiency. The higher pulse frequency also increased the collection efficiency, especially for submicron particles.